The Role of Local Government in Implementing Supervising Social Responsibility - Ramadhan, Khaidir; Espa, Vitriyan; Heniwati, Elok (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to explore the important role of local government in Supervising Social Responsibility (CSR) carried out by Micro, Small, and Medium Enterprises (MSMEs) to the community through digitalization located in Pontianak City using Qualitative research methods with a case study approach. The data collected and processed came from in-depth interviews with related parties such as local government, MSME entrepreneurs and local community views and the use of Literature Review in data processing that will be used in this article. The results of the study indicate that digitalization plays an important role in facilitating the process and transparency of CSR implementation and the role of local government in providing a digital platform that allows reporting in digital form in increasing the effectiveness and quality of CSR distribution and information to the community. This study also underlines the importance of collaboration between the government, MSMEs, and the community in encouraging the sustainable growth of a business at the local level